Medical Life in the First Abbasid Era 132-232 AH / 750-847 AD (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The science of medicine is one of the natural sciences that has matured significantly, and its branches were developing and growing and the steps of development were accelerating so that doctors of the Abbasid era could discover treatments and write books and contribute to the recovery of a large number of patients. They poured money to translate medical literature because of the role of this science in the progress and development of nations.The research deals with medical schools at the time of the Abbasids, and how the Abbasids were interested in natural sciences, methods of therapy, the most important medical families, in addition to pharmacy and its development, and the bimaristans and their attachments.